Archosauriform remains from the Lower Triassic Sanga do Cabral Formation of Brazil. Issue 6 (2nd November 2021) - De-Oliveira, Tiane M.; Kerber, Leonardo; França, Marco Aurélio Gallo De; Pinheiro, Felipe L.
ABSTRACT: Early Triassic archosauriform remains are often related to the Proterosuchidae and the Erythrosuchidae, common stem-archosaurs in the aftermath of the end-Permian extinction event. South American proterosuchid remains are rare, with only a few specimens from the Lower Triassic Sanga do Cabral Formation briefly mentioned in literature. The Lower Triassic Sanga do Cabral Formation has a growing fossil record, thus far composed of procolophonids, temnospondyls, and early-branching archosauromorphs. In this work, new materials referred to cf. Chasmatosuchus and cf. Proterosuchus (Archosauriformes) are described, representing the first conclusive archosauriform records from the Lower Triassic of Brazil. Proterosuchids are among the stratigraphically oldest Archosauriformes, with their earliest unambiguous occurrences coming from the uppermost Permian of Russia. This clade is widely spread among well-explored Lower Triassic formations, flourishing during the recovery phase from the end-Permian mass extinction. The presence of non-archosaurian archosauriforms in southwestern Gondwana reinforces the rapid diversification of archosauromorphs during the Early Triassic. The Sanga do Cabral Formation fossil assemblage is becoming important for understanding how the initial adaptive radiation of archosauromorphs took place.